2020
DOI: 10.3390/ijerph17197195
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Insulin Resistance and Cardiovascular Disease Risk: A Community-Based Cross-Sectional Study among Taiwanese People Aged over 50 Years

Abstract: Background and Aims: Previous studies have implied that insulin resistance (IR) could represent a major underlying abnormality leading to cardiovascular disease (CVD). The aim of this study was to evaluate the relationships between IR (estimated by the homeostasis model assessment of IR (HOMA-IR) index) and CVD risk among middle-aged and elderly Taiwanese individuals. Methods: In this cross-sectional, community-based study, a total of 320 participants were interviewed to collect demographical parameters and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Glucose homeostasis is a key marker of cardiometabolic health of individuals (36). We found that fasting glucose levels, fasting insulin levels, and AUCs of glucose and insulin were similar among groups after intervention (p > 0.05).…”
Section: Effects Of Interventions On Glucose Homeostasismentioning
confidence: 65%
“…Glucose homeostasis is a key marker of cardiometabolic health of individuals (36). We found that fasting glucose levels, fasting insulin levels, and AUCs of glucose and insulin were similar among groups after intervention (p > 0.05).…”
Section: Effects Of Interventions On Glucose Homeostasismentioning
confidence: 65%
“…Blood glucose parameters are related to diabetes. A recent nationwide epidemiological data demonstrated that elevated FPG increase the risk of CVD ( Kaneko et al, 2021 ); each 1% higher HbA1c, independent of diabetes status, is associated with an 18% greater risk of myocardial infarction ( de Jong et al, 2020 ); HOMA−IR is positive correlation with CVD risk ( Lu et al, 2020 ). This meta−analysis observed that RYR preparations significantly reduced the levels of FPG, HbA1c and HOMA−IR, indicating its promising application in improving diabetes and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER) cohort showed that insulin and HOMA-IR are not associated with an increased risk of incident CVD in elderly people without diabetes ( 37 ). In another study conducted by Lu et.al ( 38 ), the association between HOAMA-IR and a person's risk of CVD using the Framingham risk score (FRS) was evaluated by Taiwanese people aged ≥50 years. They found that HOMA-IR >1.15 were significantly associated with a high level of FRS (≥ 20%) but it is not recommended to use solely for evaluating the CVD risk because of the low level of the areas under the curve (0.627).…”
Section: Discussionmentioning
confidence: 99%